Compulsory Community Treatment Orders in New Zealand and the provision of care: An examination of national databases and predictors of outcome - Ben Beaglehole; Giles Newton-Howes; Chris Frampton (Elsevier, 2021)
Background: Compulsory Community Treatment Orders (CTOs) are contentious because they impose severe restrictions on individuals in community settings. The existing evidence for CTOs is constrained by ethical and methodological limitations and may not support usual clinical practise. This study examines the effectiveness of CTOs using routine data in the New Zealand context. Methods: Ministry of Health, New Zealand databases provided demographic, service use, and medication dispensing data for all individuals placed on a CTO between 2009 and 2018. We examined the effectiveness of CTOs through a comparison of psychiatric endpoints identified as useful in the literature according to CTO status. Further analyses examined the moderating influences of age, sex, ethnicity, and diagnosis on outcome. Findings: 14,726 patients were placed under a CTO over the 10 year period between 1 January 2009 and 31 December 2018. Patients on CTOs experienced a reduced frequency of admissions (rate ratio of 0∙94, 95% CI 0.93-0.95, p<0.01) reduced admission days (rate ratio 0∙97, 95% CI 0.97-0.98 p<0∙01), increased frequency of psychiatric community contacts (rate ratio 3∙03, 95% CI 3.02-3.03 p<0.01), and increased dispensing of psychiatric medication (rate ratio 2.27, 95% CI 2.27-2.28, p<0.01). When sub-group analyses were undertaken, the association between treatment under a CTO and reduced admission frequency was only present for those with Psychotic Disorders. Interpretation: CTOs in New Zealand are associated with increased community care, and increased dispensing of psychiatric medication. Patients with Psychotic Disorders also experienced reduced frequency and length of admissions whilst under a CTO. Funding: No specific funding was received for this study.